Cross-Disciplinary Advances in Human Computer Interaction 2009
DOI: 10.4018/978-1-60566-142-1.ch003
|View full text |Cite
|
Sign up to set email alerts
|

From Beliefs to Success

Abstract: The technology acceptance model (TAM) is a popular model for the prediction of information systems acceptance behaviors, defining a causal linkage between beliefs, attitudes, intentions, and the usage of information technologies. Since its inception, numerous studies have utilized the TAM, providing empirical support for the model in both traditional and Internet-based computing settings. This chapter describes a research study that utilizes an adaptation of the TAM to predict successful Web page development, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
1
2
1
Order By: Relevance
“…In this study, the relationship between gender and the resistance of employees to IT was not significant. This finding is contrasted by other studies (Bax & McGill, 2009;Chiu et al, 2001), but on a par with the findings of Viswanath Venkatesh et al (2011), who stated that gender had no impact on the use of computers. The result regarding gender in this study also did not comply with the other studies in the literature.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In this study, the relationship between gender and the resistance of employees to IT was not significant. This finding is contrasted by other studies (Bax & McGill, 2009;Chiu et al, 2001), but on a par with the findings of Viswanath Venkatesh et al (2011), who stated that gender had no impact on the use of computers. The result regarding gender in this study also did not comply with the other studies in the literature.…”
Section: Discussioncontrasting
confidence: 99%
“…Age did not significantly influence resistance to IT in this study, and this finding is consistent with the study of Bax and McGill (2009), whereas some researchers reported that age had an effect on the intention of physicians to use electronic records (Chiu et al, 2001;Viswanath Venkatesh et al, 2011;Walter & Lopez, 2008). One reason can be the average age of personnel in the examined organization as they were mostly mid-aged.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations